Disparities in the management of paediatric splenic injury. Issue 3 (2nd October 2018) - Warwick, A. M.; Jenks, T.; Fisher, R.; Garrett‐Cox, R.; Lecky, F.; Yates, D.
Abstract : Background: The non‐operative management of splenic injury in children is recommended widely, and is possible in over 95 per cent of episodes. Practice appears to vary between centres. Methods: The Trauma Audit and Research Network (TARN) database was interrogated to determine the management of isolated paediatric splenic injuries in hospitals in England and Wales. Rates of non‐operative management, duration of hospital stay, readmission and mortality were recorded. Management in paediatric surgical hospitals was compared with that in adult hospitals. Results: Between January 2000 and December 2015 there were 574 episodes. Children treated in a paediatric surgical hospital had a 95·7 per cent rate of non‐operative management, compared with 75·5 per cent in an adult hospital ( P < 0·001). Splenectomy was done in 2·3 per cent of children in hospitals with a paediatric surgeon and in 17·2 per cent of those treated in an adult hospital ( P < 0·001). There was a significant difference in the rate of non‐operative management in children of all ages. There was some improvement in non‐operative management in adult hospitals in the later part of the study, but significant ongoing differences remained. Conclusion: The management of children with isolated splenic injury is different depending on where they are treated. The rate of non‐operative management is lower in hospitals without a paediatric surgeon present. Abstract : Better in hospitals with a paediatric surgeon